A Distinctive Structural Twist in the Aminoimidazole Alkaloids from a Calcareous Marine Sponge: Isolation and Characterization of Leucosolenamines A and B - Ralifo, Paul (2007)
Bioassay-guided fractionation of Papua New Guinea collections of Leucosolenia sp. resulted in the isolation of the novel compounds leucosolenamines A (5) and B (6) and the known compound thymidine (7). Compound 5 contains a 2-aminoimidazole core substituted at C-4 and C-5 by an N,N-dimethyl-5,6-diaminopyrimidine-2,4-dione and a benzyl group, respectively. Compound 6 retains the same core structure; however C-4 is substituted by a 5,6-diamino-1,3-dimethyl-4-(methylimino)-3,4-dihydropyrimidin-2(1H)-one moiety. This substitution pattern is unique and has never been observed in calcareous imidazole alkaloid chemistry. Leucosolenamine A (5) was mildly cytotoxic against the murine colon adenocarcinoma C-38 cell line.